High-strength corrosion-resistant plastic bucket and preparation method thereof
By treating modified calcium carbonate and chopped glass fiber, combined with gradient temperature control and pressure molding processes, high-strength corrosion-resistant plastic buckets are prepared, solving the problems of insufficient transportation and corrosion resistance of existing plastic buckets, and improving performance and service life.
Patent Information
- Application Number
- CN202511946336.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-22
- Publication Date
- 2026-02-06
AI Technical Summary
Existing plastic buckets are prone to cracking and breakage during logistics and transportation due to insufficient tensile strength and impact toughness. The handles are also prone to deformation or breakage when suspended under load, and their corrosion resistance is insufficient, posing a risk of leakage.
High-strength, corrosion-resistant plastic buckets were prepared by coating modified calcium carbonate, pretreating with chopped glass fiber, adjusting the proportions of each component, and combining gradient temperature control and a three-stage pressure molding process.
It improves the tensile strength and impact resistance of plastic buckets, reduces the breakage rate during transportation, enhances the suspension stability of handles, adapts to the storage of acidic and alkaline chemicals, extends service life, and reduces production costs.
Smart Images

Figure CN121471625A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application relates to the technical field of high-performance plastic barrels, in particular to a high-strength corrosion-resistant plastic barrel and a preparation method thereof. BACKGROUND
[0002] With the rapid development of chemical industry, logistics, warehousing and the like, plastic barrels have become the core packaging and transportation carriers for various products such as liquid chemicals and solid materials due to the advantages of light weight, controllable cost, convenient forming and the like, and the application scenarios cover industrial production, commercial circulation, daily life and the like, and the market demand continues to rise. Among them, polyethylene-based and polypropylene-based plastic barrels have become one of the most widely used plastic barrel types due to good processing performance and chemical stability.
[0003] The inevitable falling, collision, stacking and extrusion and the like in the logistics transportation process put high requirements on the mechanical properties of the plastic barrels. However, due to the insufficient structural integrity of the existing products, the tensile strength and impact toughness are limited, and when the barrels are subjected to moderate-intensity falling or collision, the barrel body is prone to cracking and damage, especially when loading dangerous materials such as chemicals, the leakage risk is extremely high, which not only causes economic losses, but also may cause safety accidents and environmental pollution.
[0004] The lifting handle is prone to obvious load deformation when suspending and loading the rated capacity of heavy objects or repeatedly carrying and using, and even breakage in severe cases. This not only reduces the carrying efficiency, but also may cause the barrel to tip over due to the failure of the lifting handle, further increasing the risk of material leakage or barrel damage.
[0005] Based on this, the application designs a high-strength corrosion-resistant plastic barrel and a preparation method thereof to solve the above problems. SUMMARY
[0006] In view of the above-mentioned shortcomings of the prior art, the application provides a preparation method of a high-strength corrosion-resistant plastic barrel, comprising the following steps:
[0007] S1. The calcium carbonate is heated to 70-85 DEG C, and then a silane coupling agent is added and stirred; polyethylene wax is added, and the temperature is raised to 90-100 DEG C, and stirring is performed to obtain coated modified calcium carbonate;
[0008] S2. The chopped glass fiber is dried, and then calcium stearoyl lactate is added after cooling, and stirring is performed to obtain reinforced fiber;
[0009] S3. Cashew phenol and talcum powder are mixed, and oxidized polyethylene wax is added, and stirring is performed for 15-20 min to obtain a corrosion-resistant agent;
[0010] S4. Maleic anhydride grafted polypropylene is added to the base resin, and stirring is performed to form an activated resin;
[0011] S5. The activated resin is heated to 90-105℃, and 1.2-1.5 parts of pigment, 4-6 parts of reinforcing fiber, 6-10 parts of coated modified calcium carbonate, and 5-8 parts of corrosion-resistant agent are added in sequence, and stirred for 25-35 min to obtain a mixed resin;
[0012] S6. The mixed resin is fed into a double-screw extruder, and after extrusion, it is air-cooled and cut into particles to obtain a master batch with a particle size of 2-3 mm, which is naturally cooled to room temperature;
[0013] S7. The master batch is added to the barrel of an injection molding machine;
[0014] S8. After the cavity is filled, pressure holding and cooling are performed to obtain a barrel body;
[0015] S9. The barrel body is trimmed, first heated at 80-90℃ for 1.5-2.5 h, then cooled to 40-50℃, and cooled to room temperature to obtain a high-strength corrosion-resistant plastic barrel.
[0016] Further, S1 is specifically: adding heavy calcium carbonate into a high-speed mixer, heating to 70-85℃, first adding 0.8-1.5% of silane coupling agent KH570 based on the mass of calcium carbonate, stirring at a speed of 1000-1200 r / min for 10-15 min; then adding 3-5% of polyethylene wax based on the mass of calcium carbonate, heating to 90-100℃, increasing the speed to 1300-1500 r / min, stirring for 20-25 min to make the polyethylene wax melt and coat on the surface of the calcium carbonate in situ, and cooling to room temperature to obtain coated modified calcium carbonate.
[0017] Further, S2 is specifically: drying the chopped glass fiber in a hot air oven at 110-130℃ for 3-5 h, cooling to 55-67℃, and then adding 0.5-1% of calcium stearoyl lactate based on the mass of the fiber, stirring at a speed of 300-500 r / min for 5-8 min to obtain the reinforcing fiber.
[0018] Further, S3 is specifically: mixing cardanol and talc powder at a mass ratio of 5:2-3, adding 0.3-0.5% of oxidized polyethylene wax based on the total mass of the two, stirring at a speed of 600-800 r / min at 60-70℃ for 15-20 min to obtain the corrosion-resistant agent.
[0019] Further, the base resin is composed of 55-70% polypropylene and 30-45% high-density polyethylene.
[0020] Further, S6 is specifically: the mixed resin is sent into a double screw extruder, low temperature gradient temperature control is adopted: 130-150 DEG C in the first area, 150-165 DEG C in the second area, 165-175 DEG C in the third area, the temperature of the head is 160-170 DEG C, the screw rotation speed is 220-280 r / min, after extrusion, wind cooling is carried out, and the master batch with a particle size of 2-3 mm is obtained, and natural cooling is carried out to room temperature.
[0021] Further, S7 is specifically: the master batch is added into the cylinder of an injection molding machine, the cylinder temperature is 150-170 DEG C in the first area, 170-185 DEG C in the second area, 185-195 DEG C in the third area, the nozzle temperature is 180-190 DEG C, after melting, three-stage gradient pressure filling is adopted: the first stage injection pressure is 60-80 MPa, the injection speed is 30-50 mm / s; the second stage injection pressure is 80-100 MPa, the injection speed is 50-70 mm / s; the third stage injection pressure is 50-70 MPa, the injection speed is 20-30 mm / s.
[0022] Further, S8 is specifically: after the cavity is filled, dynamic pressure maintaining is started: the initial pressure maintaining pressure is 80-90 MPa, maintaining for 5-8 s; then reduced to 50-60 MPa, maintaining for 10-15 s; then reduced to 30-40 MPa, maintaining for 5-8 s; the cooling time is 25-40 s, the cooling water temperature is 20-30 DEG C, and the barrel body is obtained.
[0023] Further, S9 is specifically: the trimming machine is used to remove the sprue and excess corner materials, the barrel body is placed into an oven, first 80-90 DEG C heat preservation for 1.5-2.5 h, then the temperature is reduced to 40-50 DEG C at a rate of 5-10 DEG C / h, and natural cooling is carried out to room temperature, and the high-strength corrosion-resistant plastic barrel is obtained.
[0024] A high-strength corrosion-resistant plastic barrel prepared according to the preparation method.
[0025] Compared with the prior art, the present application has the following beneficial effects:
[0026] 1、The present application makes the plastic barrel obtain excellent and stable mechanical properties through the preparation of coated modified calcium carbonate, the pretreatment of chopped glass fiber and the adjustment of the proportion of each component. The tensile strength is large, the impact resistance is strong, the common scenes such as falling and collision in logistics transportation can be handled calmly, the damage rate in the transportation process is greatly reduced, the enterprise after-sales loss and user use risk are reduced; at the same time, the load suspension stability of the handle is good, even if heavy objects are loaded, the handle is not easy to deform, the long-term repeated use demand of industrial, chemical and other fields can be met, the product service life is prolonged, and the user experience is improved.
[0027] 2、The corrosion-resistant agent designed in the application has good synergy with the base resin and the modified filler, can be widely adapted to the packaging and storage requirements of chemicals such as acids and bases, does not need to adjust the production formula separately for different media, simplifies the production process, expands the application scenarios of the product, and enhances the market applicability of the product in the chemical, pharmaceutical, environmental protection and other industries.
[0028] 3、The application realizes the synchronous optimization of mechanical properties and corrosion resistance by precise proportioning of components and organic combination of process links. Without increasing the amount of expensive reinforcing materials for the pursuit of high strength, and without sacrificing product toughness for the improvement of corrosion resistance, the raw material cost and production energy consumption are effectively controlled under the premise of ensuring that the comprehensive performance of the product meets the standard, and the balance between performance advantage and economic benefit is realized. BRIEF DESCRIPTION OF DRAWINGS
[0029] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the drawings needed to be used in the embodiments or the prior art description will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present application, and other drawings can be obtained by those skilled in the art without creative labor on the basis of these drawings.
[0030] Figure 1 A high-strength corrosion-resistant plastic bucket of the present application Figure 1 ;
[0031] Figure 2 A high-strength corrosion-resistant plastic bucket of the present application Figure 2 . DETAILED DESCRIPTION
[0032] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are some of the embodiments of the present application, not all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the present application.
[0033] Embodiment 1: The present embodiment provides a preparation method of a high-strength corrosion-resistant plastic bucket, comprising the following steps:
[0034] S1. Heavy calcium carbonate (Lingshou County Mountain River Mine Product Processing Plant, 325 mesh) was added to a high-speed mixer and warmed to 85°C. 1.5% silane coupling agent KH570 based on the mass of the calcium carbonate was added first, and stirred at 1200 r / min for 15 min. Then 5% polyethylene wax based on the mass of the calcium carbonate was added, and the temperature was raised to 100°C. The stirring speed was increased to 1500 r / min, and the polyethylene wax was allowed to melt and coat the surface of the calcium carbonate in situ. After cooling to room temperature, the coated modified calcium carbonate was obtained;
[0035] S2. Cut glass fibers (Shandong Futai Fiber Co., Ltd., 9-13 μm) were placed in a hot air oven and dried at 130°C for 5 h. After cooling to 67°C, 1% calcium stearoyl lactate based on the mass of the fibers was added, and stirred at 500 r / min for 8 min to obtain the reinforcing fibers;
[0036] S3. Cashew phenol (Shanghai Hongzhuang Chemical Technology Co., Ltd.) was mixed with talc powder at a mass ratio of 5:3. 0.5% oxidized polyethylene wax (Jinan Yuyi Chemical Co., Ltd.) based on the total mass of the two was added, and stirred at 70°C and 800 r / min for 20 min to obtain the corrosion-resistant agent;
[0037] S4. The base resin was added to a double-shaft paddle mixer and stirred at 500 r / min and 75°C for 18 min. 2.4% of the activator maleic anhydride grafted polypropylene (Dongguan Shenghao Plastic Raw Material Co., Ltd.) based on the mass of the base resin was added, and the stirring was continued for 12 min to form the activated resin;
[0038] The base resin was composed of 70% polypropylene (Jiangsu Lixing Youxin Material Co., Ltd.) + 30% high-density polyethylene (Suzhou Guoya New Material Co., Ltd.);
[0039] S5. 83 parts of the activated resin were warmed to 105°C, and the stirring speed was increased to 1000 r / min. 1.5 parts of the pigment, 6 parts of the reinforcing fibers, 10 parts of the coated modified calcium carbonate, and 8 parts of the corrosion-resistant agent were added in sequence, and stirred for 35 min to obtain the mixed resin;
[0040] The pigment was selected from rutile titanium dioxide CR828 or Unipure P0080A aniline black.
[0041] S6. The mixed resin was fed into a double-screw extruder, and a low-temperature gradient temperature control was adopted: zone 1 130-150°C, zone 2 150-165°C, zone 3 165-175°C, die temperature 160-170°C, and screw speed 280 r / min. After extrusion, the particles were air-cooled and cut into granules with a particle size of 2-3 mm, and then naturally cooled to room temperature;
[0042] S7. Add the masterbatch into the injection molding machine cylinder, the cylinder temperature zone 1 150-170℃, zone 2 170-185℃, zone 3 185-195℃, nozzle temperature 180-190℃, after melting, use three-stage gradient pressure to fill the mold: the first stage (40% of the cavity is filled) injection pressure 80 MPa, injection speed 50 mm / s; the second stage (90% of the cavity is filled) injection pressure 100 MPa, injection speed 70 mm / s; the third stage (the cavity is full) injection pressure 70 MPa, injection speed 30 mm / s;
[0043] S8. After the cavity is full, start dynamic pressure keeping: initial pressure keeping pressure 90 MPa, keep for 8 s; then reduce to 60 MPa, keep for 15 s; then reduce to 40 MPa, keep for 8 s; cooling time 40 s, cooling water temperature 30℃, get the barrel body;
[0044] S9. Use a trimming machine to remove the sprue and excess edge material, put the barrel body into an oven, first 90℃ for 2.5h, then reduce the temperature to 50℃ at a rate of 10℃ / h, naturally cool to room temperature, get the high-strength corrosion-resistant plastic barrel.
[0045] Example 2: The present embodiment provides a method for preparing a high-strength corrosion-resistant plastic barrel, comprising the following steps:
[0046] S1. Add heavy calcium carbonate (Lingshou County Mountain River Mineral Product Processing Factory, 325 mesh) into a high-speed mixer, heat to 70℃, first add 0.8% of silane coupling agent KH570 based on the mass of calcium carbonate, stir at 1000 r / min for 10 min; then add 3% of polyethylene wax based on the mass of calcium carbonate, heat to 90℃, increase the stirring speed to 1300 r / min, stir for 20 min, so that the polyethylene wax is melted and coated on the surface of the calcium carbonate in situ, cool to room temperature to get the coated modified calcium carbonate;
[0047] S2. Put the chopped glass fiber (Shandong Futai Fiber Co., Ltd., 9-13 μm) into a hot air oven, dry at 110℃ for 3h, cool to 55℃, then add 0.5% of calcium stearoyl lactate based on the mass of the fiber, stir at 300 r / min for 5 min, get the reinforcing fiber;
[0048] S3. Mix cardanol (Shanghai Hongzhuang Chemical Technology Co., Ltd.) and talcum powder according to the mass ratio of 5:2, add 0.3% of oxidized polyethylene wax (Jinan Yuyi Chemical Co., Ltd.) based on the total mass of the two, stir at 60℃ and 600 r / min for 15 min, get the corrosion-resistant agent;
[0049] S4. The base resin is added to a double-shaft paddle mixer, stirred at a speed of 300 r / min and a temperature of 60°C for 12 min, 1.4% of the base resin mass of an activator, maleic anhydride grafted polypropylene (Dongguan Shenghao Plastic Raw Material Co., Ltd.) is added, and stirring is continued for 8 min to form an activated resin;
[0050] The base resin is composed of 55% polypropylene (Jiangsu Lixing Youxin Material Co., Ltd.) + 45% high-density polyethylene (Suzhou Guoya New Material Co., Ltd.);
[0051] S5. 70 parts of the activated resin are heated to 90°C, the speed is increased to 800 r / min, 1.2 parts of a pigment, 4 parts of a reinforcing fiber, 6 parts of a coated modified calcium carbonate, and 5 parts of a corrosion-resistant agent are added in sequence, and stirring is performed for 25 min to obtain a mixed resin;
[0052] The pigment is selected from Ultramarine Blue G of Germany Lanxess.
[0053] S6. The mixed resin is fed into a double-screw extruder, a low-temperature gradient temperature control is adopted: zone 1 130-150°C, zone 2 150-165°C, zone 3 165-175°C, die temperature 160-170°C, screw speed 220 r / min, and after extrusion, air cooling and granulation are performed to obtain a master batch with a particle size of 2-3 mm, which is naturally cooled to room temperature;
[0054] S7. The master batch is added to the barrel of an injection molding machine, the barrel temperature is zone 1 150-170°C, zone 2 170-185°C, zone 3 185-195°C, the nozzle temperature is 180-190°C, after melting, a three-stage gradient pressure filling is adopted: the first stage (30% of the cavity is filled) injection pressure 60 MPa, injection speed 30 mm / s; the second stage (80% of the cavity is filled) injection pressure 80 MPa, injection speed 50 mm / s; the third stage (the cavity is fully filled) injection pressure 50 MPa, injection speed 20 mm / s;
[0055] S8. After the cavity is fully filled, dynamic pressure holding is started: the initial pressure holding pressure is 80 MPa, which is maintained for 5 s; then it is reduced to 50 MPa, which is maintained for 10 s; then it is reduced to 30 MPa, which is maintained for 5 s; the cooling time is 25 s, and the cooling water temperature is 20°C, thereby obtaining a barrel body;
[0056] S9. The ejection gate and excess edge material are removed by using an edge trimming machine, the barrel body is placed in an oven, first heated at 80°C for 1.5 h, then cooled at a rate of 5°C / h to 40°C, and naturally cooled to room temperature, thereby obtaining a high-strength corrosion-resistant plastic barrel.
[0057] Example 3: A preparation method of a high-strength corrosion-resistant plastic barrel is provided, which comprises the following steps:
[0058] S1. Heavy calcium carbonate (Lingshou County Mountain River Mine Product Processing Plant, 325 mesh) was added into a high-speed mixer and warmed to 73°C. 1.1% of silane coupling agent KH570 based on the mass of the calcium carbonate was added first, and stirred at 1000 r / min for 12 min. Then 3.6% of polyethylene wax based on the mass of the calcium carbonate was added, and the temperature was raised to 92°C. The stirring speed was increased to 1300 r / min, and the polyethylene wax was allowed to melt and coat the surface of the calcium carbonate in situ. After cooling to room temperature, the coated modified calcium carbonate was obtained;
[0059] S2. The chopped glass fiber (Shandong Futai Fiber Co., Ltd., 9-13 μm) was dried in a hot air oven at 114°C for 4 h, and then cooled to 59°C. 0.9% of calcium stearoyl lactate based on the mass of the fiber was added, and stirred at 350 r / min for 6 min to obtain the reinforcing fiber;
[0060] S3. Cashew phenol (Shanghai Hongzhuang Chemical Technology Co., Ltd.) was mixed with talc powder at a mass ratio of 5:2, and 0.5% of oxidized polyethylene wax (Jinan Yuyi Chemical Co., Ltd.) based on the total mass of the two was added. The mixture was stirred at 66°C and 670 r / min for 17 min to obtain the corrosion-resistant agent;
[0061] S4. The base resin was added into a double-shaft paddle mixer and stirred at 340 r / min and 68°C for 15 min. 2.1% of the activator maleic anhydride grafted polypropylene (Dongguan Shenghao Plastic Raw Material Co., Ltd.) based on the mass of the base resin was added, and the stirring was continued for 10 min to form the activated resin;
[0062] The base resin was composed of 63% polypropylene (Jiangsu Lixing Youxin Material Co., Ltd.) + 37% high-density polyethylene (Suzhou Guoya New Material Co., Ltd.);
[0063] S5. 21 parts of the activated resin were warmed to 97°C, and the stirring speed was increased to 800 r / min. 1.2 parts of the pigment, 5.5 parts of the reinforcing fiber, 8.7 parts of the coated modified calcium carbonate, and 6.3 parts of the corrosion-resistant agent were added in sequence, and stirred for 32 min to obtain the mixed resin;
[0064] The pigment was selected from Ultramarine Blue G of Lanxess, Germany.
[0065] S6. The mixed resin was fed into a double-screw extruder, and a low-temperature gradient temperature control was adopted: 130-150°C in the first zone, 150-165°C in the second zone, 165-175°C in the third zone, and 160-170°C in the die head. The screw rotation speed was 270 r / min. After extrusion, the product was air-cooled and pelletized. The master batch with a particle size of 2-3 mm was obtained, and was naturally cooled to room temperature;
[0066] S7. Add the masterbatch into the injection molding machine cylinder, the cylinder temperature zone 1 150-170℃, zone 2 170-185℃, zone 3 185-195℃, nozzle temperature 180-190℃, after melting, use three-stage gradient pressure to fill the mold: the first stage (35% of the cavity filling) injection pressure 70 MPa, injection speed 30 mm / s; the second stage (80% of the cavity filling) injection pressure 92 MPa, injection speed 50 mm / s; the third stage (full cavity) injection pressure 65 MPa, injection speed 25 mm / s;
[0067] S8. After the cavity is full, start the dynamic pressure holding: the initial pressure holding pressure is 88 MPa, which is maintained for 6 s; then reduced to 52 MPa, maintained for 11 s; then reduced to 37 MPa, maintained for 6 s; cooling time 31 s, cooling water temperature 25℃, get the barrel body;
[0068] S9. Use the trimming machine to remove the gate and excess edge material, put the barrel body into the oven, first 87℃ for 2.5h, then reduce the temperature to 47℃ at a rate of 6℃ / h, and naturally cool to room temperature, get the high-strength corrosion-resistant plastic barrel.
[0069] Example 4: The present embodiment provides a method for preparing a high-strength corrosion-resistant plastic barrel, comprising the following steps:
[0070] S1. Add heavy calcium carbonate (Lingshou County Mountain River Mineral Product Processing Factory, 325 mesh) into a high-speed mixer, heat to 79℃, first add 0.9% of silane coupling agent KH570 based on the mass of calcium carbonate, stir at 1200r / min for 14min; then add 4.1% of polyethylene wax based on the mass of calcium carbonate, heat to 97℃, increase the stirring speed to 1300r / min, stir for 22min, so that the polyethylene wax is melted and coated on the surface of the calcium carbonate in situ, and then cool to room temperature to obtain coated modified calcium carbonate;
[0071] S2. Put the chopped glass fiber (Shandong Futai Fiber Co., Ltd., 9-13μm) into a hot air oven, dry at 117℃ for 4h, then cool to 61℃, add 0.6% of calcium stearoyl lactate based on the mass of the fiber, stir at 380r / min for 6min, to obtain the reinforcing fiber;
[0072] S3. Mix cardanol (Shanghai Hongzhuang Chemical Technology Co., Ltd.) and talcum powder at a mass ratio of 5:3, add 0.5% of oxidized polyethylene wax (Jinan Yuyi Chemical Co., Ltd.) based on the total mass of the two, stir at 62℃ and 600r / min for 17min, to obtain the corrosion-resistant agent;
[0073] S4. The base resin is added to a double-shaft paddle mixer, stirred at a speed of 300 r / min and a temperature of 61 °C for 17 min, 2.2% of the base resin mass of an activator, maleic anhydride grafted polypropylene (Dongguan Shenghao Plastic Raw Material Co., Ltd.) is added, and stirring is continued for 9 min to form an activated resin;
[0074] The base resin is composed of 64% polypropylene (Jiangsu Lixing Youxin Material Co., Ltd.) + 31% high-density polyethylene (Suzhou Guoya New Material Co., Ltd.);
[0075] S5. 80 parts of the activated resin are heated to 102 °C, the speed is increased to 900 r / min, 1.4 parts of a pigment, 5 parts of a reinforcing fiber, 7 parts of a coated modified calcium carbonate, and 6 parts of a corrosion-resistant agent are added in sequence, and stirring is performed for 31 min to obtain a mixed resin;
[0076] The pigment is selected from Ultramarine Blue G of Germany Lanxess.
[0077] S6. The mixed resin is fed into a double-screw extruder, a low-temperature gradient temperature control is adopted: Zone 1 130-150 °C, Zone 2 150-165 °C, Zone 3 165-175 °C, die temperature 160-170 °C, screw speed 250 r / min, after extrusion, air cooling and granulation are performed to obtain a master batch with a particle size of 2-3 mm, and natural cooling to room temperature is performed;
[0078] S7. The master batch is added to the barrel of an injection molding machine, the barrel temperature is Zone 1 150-170 °C, Zone 2 170-185 °C, Zone 3 185-195 °C, the nozzle temperature is 180-190 °C, after melting, a three-stage gradient pressure filling is adopted: the first stage (cavity filling 38%) injection pressure 72 MPa, injection speed 35 mm / s; the second stage (cavity filling 86%) injection pressure 91 MPa, injection speed 66 mm / s; the third stage (cavity full filling) injection pressure 64 MPa, injection speed 25 mm / s;
[0079] S8. After the cavity is fully filled, dynamic pressure holding is started: initial pressure holding pressure 86 MPa, holding for 7 s; then reduced to 53 MPa, holding for 12 s; then reduced to 31 MPa, holding for 7 s; cooling time 30 s, cooling water temperature 25 °C, to obtain a barrel body;
[0080] S9. The gate and excess edge and corner materials are removed by using an edge trimming machine, the barrel body is placed in an oven, first heat preservation at 86 °C for 2 h, then cooling at a rate of 7 °C / h to 42 °C, and natural cooling to room temperature, to obtain a high-strength corrosion-resistant plastic barrel.
[0081] Comparative Example 1: The difference between this comparative example and Example 3 is that in S1, polyethylene wax is not added.
[0082] Comparative Example 2: The difference between this comparative example and Example 3 is that S2 is not performed, and directly selected short glass fiber as reinforcing fiber.
[0083] Comparative Example 3: The difference between this comparative example and Example 3 is that in S3, the mass ratio of cardanol to talc is 1:4.
[0084] Comparative Example 4: The difference between this comparative example and Example 3 is that in S1, polyethylene wax is not added; S2 is not performed, and directly selected short glass fiber as reinforcing fiber; in S3, the mass ratio of cardanol to talc is 1:4.
[0085] Experimental Example 1: The tensile strength (MPa) and elongation at break (%) of the plastic barrels prepared in the examples and comparative examples of the present application were detected according to GB / T 1040.2-2022.
[0086] Experimental Example 2: The impact resistance of the plastic barrels was detected according to GB / T 4857.11-2005.
[0087] The inner content is sand, and the loading is 95% of the rated capacity, and the density is 1.6 g / cm 3 The number of test samples is 3 parallel samples; the size is 100L barrel, injection molding integrated (including handle), the fixed method is free falling (no additional fixing), and the sealing method is barrel cover screwing, torque 20N・m;
[0088] During the test, the test sample was vertically placed on the C30 concrete hard horizontal ground, and the impact positions were the barrel corner and the barrel bottom center, respectively. Each position was tested 3 times, and the total test number was 6 times. The falling height (cm) when the sample cracked was recorded.
[0089] Experimental Example 3: The load deformation rate (%) after the handle suspension load of 160 kg (15 min) was detected according to GB / T 13508-2011.
[0090] Experimental Example 4: The mass loss rate (%) and volume loss rate (%) of the plastic barrels after being immersed in the proposed chemical (3% HCl solution, 10% NaOH solution) for 30 days were detected according to GB / T 11547-2008.
[0091] The results are shown in the following table:
[0092] Item Tensile strength MPa Elongation at break % Drop height cm Load deflection rate % Mass reduction rate % Volume reduction rate % Example 1 43.1 31.6 ≥185 ≤2 ≤0.05 ≤0.2 Example 2 43.2 31.4 ≥185 ≤2 ≤0.05 ≤0.2 Example 3 43.5 31.2 ≥185 ≤2 ≤0.05 ≤0.2 Example 4 43.3 31.7 ≥185 ≤2 ≤0.05 ≤0.2 Comparative Example 1 41.7 30.5 180 2.21 0.15 ≤0.2 Comparative Example 2 35.4 31.3 150 3.24 ≤0.05 ≤0.2 Comparative Example 3 40.6 29.6 180 2.04 ≤0.05 0.17 Comparative Example 4 30.2 25.1 120 4.89 0.23 0.51
[0093] From the above table, only the polyethylene wax coating is missing, the mechanical properties fall slightly, indicating that the coating treatment of calcium carbonate has an auxiliary effect on improving the basic strength; when the chopped glass fiber is not dried and surface treated, the tensile strength and impact resistance decrease significantly, which highlights the important role of fiber pretreatment in enhancing the structural support force; adjusting the ratio of cardanol and talc in the comparative example, the elongation at break and impact resistance fluctuate, indicating that the ratio of corrosion resistant agent not only affects the corrosion resistance, but also indirectly relates to the toughness of the material; while missing multiple key processes and reasonable ratios in the comparative example, all mechanical indicators and corrosion resistance performance are significantly down, which reflects the synergistic effect between the processes and components. The loss of a single link may lead to a decline in local performance, and the loss of multiple links may cause the collapse of overall performance.
[0094] The above examples are only used to illustrate the technical solutions of the present application, but not to limit it; although the present application has been described in detail with reference to the foregoing examples, those skilled in the art should understand that the technical solutions recorded in the foregoing examples can be modified, or some technical features can be replaced by equivalents; and these modifications or replacements will not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present application.
Claims
1. A method for preparing a high-strength, corrosion-resistant plastic bucket, characterized in that, Includes the following steps: S1. Heat calcium carbonate to 70-85℃, add silane coupling agent and stir; then add polyethylene wax, heat to 90-100℃ and stir to obtain coated modified calcium carbonate; S2. Dry the chopped glass fibers, cool them, add calcium stearoyl lactylate, and stir to obtain reinforcing fibers; S3. Mix cashew phenol with talc, add oxidized polyethylene wax, and stir for 15-20 minutes to obtain a corrosion resistant agent; S4. Add maleic anhydride-grafted polypropylene to the matrix resin and stir to form an activated resin; S5. Heat 70-83 parts of activated resin to 90-105℃, and add 1.2-1.5 parts of pigment, 4-6 parts of reinforcing fiber, 6-10 parts of coated modified calcium carbonate and 5-8 parts of corrosion resistant agent in sequence. Stir for 25-35 minutes to obtain mixed resin. S6. Feed the mixed resin into a twin-screw extruder, and after extrusion, it is air-cooled and pelletized to obtain masterbatch with a particle size of 2-3 mm, which is then naturally cooled to room temperature; S7. Add the masterbatch to the injection molding machine barrel; S8. After the cavity is fully filled, pressure is maintained and cooled to obtain the barrel body; S9. Trim the edges of the bucket, first keep it at 80-90℃ for 1.5-2.5 hours, then cool it down to 40-50℃, and finally cool it to room temperature to obtain a high-strength, corrosion-resistant plastic bucket.
2. The method for preparing a high-strength, corrosion-resistant plastic bucket according to claim 1, characterized in that, S1 is specifically as follows: Add heavy calcium carbonate to a high-speed mixer and heat it to 70-85℃. First, add 0.8-1.5% of the silane coupling agent KH570 by mass of calcium carbonate and stir at 1000-1200 r / min for 10-15 min. Then, add 3-5% of the polyethylene wax by mass of calcium carbonate, heat it to 90-100℃, increase the speed to 1300-1500 r / min, and stir for 20-25 min. After the polyethylene wax melts, it coats the surface of the calcium carbonate in situ. After cooling to room temperature, the coated modified calcium carbonate is obtained.
3. The method for preparing a high-strength, corrosion-resistant plastic bucket according to claim 1, characterized in that, S2 specifically involves placing chopped glass fibers into a hot air oven and drying them at 110-130℃ for 3-5 hours. After cooling to 55-67℃, calcium stearoyl lactylate (0.5-1% of the fiber mass) is added, and the mixture is stirred at 300-500 r / min for 5-8 minutes to obtain the reinforcing fibers.
4. The method for preparing a high-strength, corrosion-resistant plastic bucket according to claim 1, characterized in that, S3 is specifically prepared by mixing cashew phenol and talc powder at a mass ratio of 5:2-3, adding 0.3-0.5% of oxidized polyethylene wax by mass of the two, and stirring at 60-70℃ and 600-800 r / min for 15-20 min to obtain a corrosion resistant agent.
5. The method for preparing a high-strength, corrosion-resistant plastic bucket according to claim 1, characterized in that, The matrix resin is composed of 55-70% polypropylene and 30-45% high-density polyethylene.
6. The method for preparing a high-strength, corrosion-resistant plastic bucket according to claim 1, characterized in that, S6 specifically involves feeding the mixed resin into a twin-screw extruder, using a low-temperature gradient temperature control: Zone 1 130-150℃, Zone 2 150-165℃, Zone 3 165-175℃, die head temperature 160-170℃, screw speed 220-280r / min, and after extrusion, the resin is air-cooled and pelletized to obtain masterbatch with a particle size of 2-3mm, which is then naturally cooled to room temperature.
7. The method for preparing a high-strength, corrosion-resistant plastic bucket according to claim 1, characterized in that, S7 specifically involves adding the masterbatch to the injection molding machine barrel. The barrel temperature is 150-170℃ in zone 1, 170-185℃ in zone 2, and 185-195℃ in zone 3. The nozzle temperature is 180-190℃. After melting, the mold is filled with three-stage gradient pressure: the first stage injection pressure is 60-80MPa and the injection speed is 30-50mm / s; the second stage injection pressure is 80-100MPa and the injection speed is 50-70mm / s; and the third stage injection pressure is 50-70MPa and the injection speed is 20-30mm / s.
8. The method for preparing a high-strength, corrosion-resistant plastic bucket according to claim 1, characterized in that, S8 specifically refers to: after the cavity is fully filled, dynamic pressure holding is activated: the initial pressure holding pressure is 80-90MPa, held for 5-8s; then it is reduced to 50-60MPa, held for 10-15s; then it is reduced to 30-40MPa, held for 5-8s; the cooling time is 25-40s, the cooling water temperature is 20-30℃, and the barrel body is obtained.
9. The method for preparing a high-strength, corrosion-resistant plastic bucket according to claim 8, characterized in that, S9 specifically involves: using a trimming machine to remove the gate and excess scrap, placing the bucket in an oven, first keeping it at 80-90℃ for 1.5-2.5 hours, then cooling it down to 40-50℃ at a rate of 5-10℃ / hour, and then allowing it to cool naturally to room temperature to obtain a high-strength, corrosion-resistant plastic bucket.
10. A high-strength, corrosion-resistant plastic bucket prepared by the preparation method according to any one of claims 1-9.